The Prescription Pattern of Chinese Herbal Products That Contain Dang-Qui and Risk of Endometrial Cancer among Tamoxifen-Treated Female Breast Cancer Survivors in Taiwan: A Population-Based Study - Wu, Chien-Tung; Lai, Jung-Nien; Tsai, Yueh-Ting (PloS one, 2014)
The increased practice of traditional Chinese medicine worldwide has raised concerns regarding herb-drug interactions. We analyzed the usage of Chinese herbal products containing dang-qui and investigated whether dang-qui therapy increases endometrial cancer risk among tamoxifen-treated breast cancer survivors in Taiwan. All patients newly diagnosed with invasive breast cancer who received tamoxifen treatment from January 1, 1998, to December 31, 2008 were selected from the National Health Insurance Research Database. The usage, frequency of service and type of Chinese herbal products containing dang-qui prescribed across the 31,970 survivors were evaluated. Logistic regression method was employed to estimate the odds ratios for utilization of Chinese herbal products containing dang-qui. Cox proportional hazard regression was performed to calculate the hazard ratio of endometrial cancer associated with dang-qui use within the cohort. Almost one in two study subjects had used dang-qui. Among 31,938 tamoxifen-treated breast cancer survivors, 157 cases of subsequent endometrial cancer were identified. The hazard ratio for development of endometrial cancer among breast cancer survivors aged 20-79 years who had taken dang-qui after tamoxifen treatment was decreased compared to survivors who had never used dang-qui (HR: 0.61, 95%CI: 0.44-0.84). To minimise potential confounding factors, women with breast cancer in the reproductive age were excluded from further analysis, and the negative relationship between dang-qui consumption and subsequent endometrial cancer among breast cancer survivors aged 55-79 years was still observed, although not significantly (HR: 0.74, 95%CI: 0.46-1.17). Dang-qui consumption is common among breast cancer survivors aged 20-79 years and seems decrease the risk of subsequent endometrial cancer after less than a cumulative dose of 7,500 mg of tamoxifen treatment.